Liberation of Protein and Antioxidative Compound from Spent Coffee Ground Through Protein Hydrolysis (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2018)
Spent coffee ground is a primary by-product obtained during soluble coffee processing and potential to be used as a high value product due to its proteincontent. The quite popular effort to utilize protein-contained material is to process it to hydrolysate which also possess antioxidant activity. This research was aimed to study the possibility of protein and antioxidative compound from spent coffee ground by means of enzymatic hydrolysis using crude papain enzymes. Crude papain was used in different concentration ranged from 2, 4 and 6% to incubate the spent coffee grounds for 2, 3, and 4 hours and then analyzed for its protein content and its antioxidant activity. Response surface methodology was employed to study the tendency of the effect of incubation time and enzymesconcentration towards hydrolysis results. The result showed that the use of crude papain was effective to liberate the protein and antioxidant compound from the spent coffee ground with its optimum condition utilized 6% of enzyme and 2 hours incubation time. At mentioned condition, it could extract up to 67.4% ofthe protein of the spent coffee ground and its hydrolysate possessed relatively high antioxidant activity.